Visual Adaptation: From Comics to Superhero Creation of Wayang - Taufiq Akbar; Dendi Pratama; Sarwanto Sarwanto; Sunardi Sunardi (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
This article discusses the fusion and blending of the concept of wayang as a traditional culture with comics and films as products of contemporary culture that gave birth to new wayang creations with sources adapted from “Avenger” superhero characters. The making of wayang avenger is to maintain the art of craftsmanship in wayang kulit, namely considering the existence of attributes in traditional wayang with the necessary adjustments to the Avenger superhero outfit. Revealing the results of research on the Avenger Creation Wayang is very important because it can explain the process of changing the shape, appearance and addition of wayang attributes as a manifestation of adaptation to traditional wayang puppets, namely wayang kulit purwa. This article attempts to provide descriptive and interpretive explanations of the visual adaptation process by the creator in the formation of wayang avenger. The approach in this study uses Erwin Panofsky’s iconographic approach with the support of art structure theory and vehicle transfer. The result is the presence of Wayang Kreasi Avenger as a form of fusion between traditional culture and contemporary culture. This development shows the love of the community for the potential of influencing traditional cultural heritage and the interaction with the potential of contemporary culture which is very strong, giving rise to the idea of adaptation as a reflection of the environment and its social structure.